Tribological Performance Investigation of a Commercial Engine Oil Incorporating Reduced Graphene Oxide as Additive - Kaleli, Hakan; Demirtas, Selman; Uysal, Veli; Karnis, Ioannis; Stylianakis, Minas M.; Anastasiadis, Spiros H.; Kim, Dae-Eun (MDPI, 2021)
We investigated the tribological behavior of commercialized, fully synthetic engine oil upon the incorporation of reduced graphene oxide in seven different concentrations between 0.01 and 0.2 wt %. Stability of the prepared samples was assessed by turbidimetry and dynamic light scattering measurements, and their tribological properties through a reciprocating tribometer, using a steel ball on special cut steel blocks. The addition of 0.02 wt % of reduced graphene oxide led to an improvement of the tribological behavior compared to the pristine engine oil, by significantly lowering the friction coefficient by 5% in the boundary lubrication regime. Both the surfaces and the reduced graphene oxide additive were thoroughly characterized by microscopic and optical spectroscopy techniques. We also verified that a protective layer was formed between the worn surfaces, due to the presence of reduced graphene oxide. Carbon accumulation and various additive elements such as Ca, Zn, S and P were detected on the rubbing surfaces of both the ball and the block through energy-dispersive X-ray spectroscopy. Finally, it was shown that the wear scar diameter on the surface of the steel ball was lower by 3%, upon testing the engine oil sample containing reduced graphene oxide at concentration 0.02 wt %, compared to the control sample.
Keywords: reduced graphene oxide; dispersion; engine oil additives; 5W-40; friction; friction coefficient; wear; tribological properties; Chemistry; Science & Technology - Other Topics; Materials Science; Physics